Superoxide Dismutase Reduces Creatinine and NGAL by Restoring Oxidative Balance during Sepsis - Jufitriani Ismy; Maimun Syukri; Dessy R. Emril; Nanan Sekarwana; Jufriady Ismy (Emerging Science Journal, 2022)
Sepsis-associated overproduction of reactive oxygen species (ROS) and nitric oxide (NO) during pathogen infection leads to overwhelming oxidative stress, which has been recognized as a primary contributor to acute kidney injury (AKI). Hence, antioxidant therapy has been widely explored in order to find an effective treatment for sepsis-related AKI, in particular by using endogenous antioxidant – superoxide dismutase (SOD). We assessed the effect of oral SOD on the alteration of AKI biomarkers (creatinine and Neutrophil Gelatinase-Associated Lipocalin – NGAL) in endotoxin-induced septic murine. The animals were assigned as a healthy control, a septic control, and three treatment groups (250, 500, and 1000 IU oral SOD). Treatment of SOD was carried out by force-feeding for 16 weeks prior to intraperitoneal injection of lipopolysaccharide (LPS). The sepsis was assessed using the murine sepsis score (MSS) after 12 hours post-LPS injection, where the changes in plasma SOD, ROS, NO, creatinine, and NGAL were measured by enzyme-linked immunosorbent assay (ELISA). During sepsis, SOD was significantly decreased from its baseline level while other biomarkers were significantly increased (p<0.05) – except for NGAL. MSS exhibited a declining trend in SOD dosage-dependent manner, and was significantly different with that of septic control group at SOD dosage of 1000 IU (p<0.05). SOD treatment with a dosage as low as 250 IU could prevent the abnormal expression of the tested biomarkers during sepsis. There were significant reduction of plasma ROS, NO, creatine and NGAL in rats treated with 1000 IU SOD. Our study suggests the protective effect of SOD against sepsis-induced AKI by scavenging ROS and NO. Doi: 10.28991/ESJ-2022-06-02-06 Full Text: PDF